Dinamika Penggunaan Bahasa Indonesia dalam Komunikasi Perikanan Pesisir: Perspektif Linguistik, Generasi, dan Kearifan Lokal di Desa Bongo dan Kelurahan Pohe - Dali, Meilina Widya; Talib, Siti Nur Fadilah Y.; Hunou, Mohamad Haikal; Sabubu, Revalina Cahyani; Andini, Putri Sesilia; Paramata, Nurain; Abuge, Nurain; Samade, Nur Syifa; Agel, Randi L.; Huko, Fadly T.; Labudu, Silvani B.; Mooduto, Eko purwanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Indonesian language plays a strategic role in fisheries activities within multilingual coastal communities. This study aims to explore the dynamics of Indonesian language use in the fisheries sector in Bongo Village and Pohe Subdistrict by examining linguistic aspects, generational differences, and local wisdom-based extension communication patterns. A qualitative descriptive approach was employed through interviews with fishermen, housewives, and educators. The findings indicate that Indonesian functions as a formal language in fisheries communication, particularly in extension services, empowerment programs, and interactions with external stakeholders. However, its effectiveness is influenced by social background, educational level, and generational differences. The integration of Indonesian and Gorontalo local language emerges as an effective communication strategy in supporting sustainable fisheries resource management.